2002
DOI: 10.1128/ec.1.6.944-953.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Localization Changes in the Trypanosoma cruzi Nucleus

Abstract: Chromosome localization in the interphase nuclei of eukaryotes depends on gene replication and transcription. Little is known about chromosome localization in protozoan parasites such as trypanosomes, which have unique mechanisms for the control of gene expression, with most genes being posttranscriptionally regulated. In the present study, we examined where the chromosomes are replicated in Trypanosoma cruzi, the agent of Chagas' disease. The replication sites, identified by the incorporation of 5-bromodeoxyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
(42 reference statements)
2
33
0
8
Order By: Relevance
“…To better understand the ultrastructural modifications after treatment with berenil, we used the TdT technique, which specifically labels DNA and was previously employed to study the T. cruzi cell cycle (Elias et al 2002). Our results showed that the kinetoplast electron-lucent areas observed in treated parasites were not labeled, thus indicating that this region did not contain decatenated circles, as initially thought.…”
Section: Resultsmentioning
confidence: 53%
“…To better understand the ultrastructural modifications after treatment with berenil, we used the TdT technique, which specifically labels DNA and was previously employed to study the T. cruzi cell cycle (Elias et al 2002). Our results showed that the kinetoplast electron-lucent areas observed in treated parasites were not labeled, thus indicating that this region did not contain decatenated circles, as initially thought.…”
Section: Resultsmentioning
confidence: 53%
“…We, along with others, have already shown that it is possible to synchronize T. cruzi epimastigote cells with hydroxyurea. 9,17,18 Hydroxyurea inhibits the nucleotide reductase enzyme, thereby consuming dNTPs. In the absence of dNTPs, DNA elongation is blocked and most of the cells are arrested very early in S phase.…”
Section: Resultsmentioning
confidence: 99%
“…We have also shown that 6 h after hydroxyurea release, cells are in the S phase, replicating their DNA. 9 Analysis of cells at 0 or 6 h after release (S phase) showed that most of these cells display the peripheral pattern for both TcOrc1/Cdc6 and TcPCNA (table 1). These numbers strongly suggest that the peripheral patterns correspond to cells whose DNA is being replicated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations